Data, attitudinal and organizational determinants of big data analytics systems use - Charlie Chen; Hoon Seok Choi; Peter Ractham (Cogent Business & Management, 2022)
This study investigates influential factors on the use of Big Data Analytics (BDA) systems in terms of data quality, organizational support, and user satisfaction. We surveyed 236 actual users of BDA systems in different industries and used the PLS-SEM method to analyze the collected data. The empirical evidence shows that data integrity and data timeliness determine data connectivity of BDA systems, which affect user satisfaction along with relational knowledge of IT personnel. The findings also indicate that user satisfaction has a positive effect on BDA system use, whereas data connectivity does not. The findings imply that user experiences appear to have a significant influence on the intention of business practitioners to use BDA systems, but data connectivity does not. Based on the empirical findings, this study provides both theoretical and practical implications for the success of BDA systems use.
Keywords: 650; big data analytics; data connectivity; user satisfaction